Political Participation in Self-Managed Social Centres. Direct Social Action and Institutionalization in Bologna City - Giannini, Vito; Pirone, Maurilio (PARTECIPAZIONE E CONFLITTO, 2019)
While regeneration is emerging as a paradigm capable of inspiring public policies and transforming lifestyles, the urban space remains a fertile ground in which collective initiatives based on activism and solidarity can emerge. The aim of this article is to describe some social and political practices in self-managed spaces and their relationship both with the wider background of the city and with local institu-tions. We argue that processes of institutionalization could affect practices of self-organization and political participation in different ways: these processes could mark the cooptation of conflicts into local administration strategies as well as open new forms of politicization around urban commons. We will present a case study, the evolution of the social centre Làbas in Bologna city, as a testing ground to explore and examine these practices and interactions. In the following paragraphs, we define the self-managed social centres, considering the processes of repression and institutionalization, and the development of new forms of political participation. Then we focus on the history of Bologna's social centres. Finally, we analyze the case study, briefly describing the process of institutionalization and the evolution of its practices.